You say you want a revolution?: radical idealism and its tragic consequences - Chirot, Daniel (Princeton University Press, 2020)
Revolution as tragedy -- Incompetence, chaos, and extremism : how more moderate forces lost control in France, Russia, Iran, and Germany -- Reaction, war, invasion, and revolutionary terror -- The tyranny of idealistic certitude and imagined utopias -- Revolutions betrayed : autocratic corruption and the end of idealistic third worldism -- Peaceful revolutions? : interpreting conservative and liberal successes and failures -- Are there lessons for us to learn?.